Dynamics of pathomorphological changes in the structural organization of the intervertebral disc at the end of the seventh and fourteenth day of experimental opioid exposure at the ultrastructural level - M. V. Pankiv; Ye. V. Paltov; Z. Z. Masna; I. V. Chelpanova; M. Ye. Kovalska (Kazimierz Wielki University, 2021)
In general, the modern literature pays attention to the issues of spine pathology and intervertebral discs. A significant percentage of vertebral disorders - scoliosis, osteochondrosis, spinal disc herniation, etc., occur as a result of exposure to various factors and manifest in changes of the intervertebral discs. The aim of our work was to study at the ultrastructural level the features of pathomorphological manifestations in the structural components of the intervertebral disc at the end of the seventh and fourteenth days of experimental opioid exposure. Materials and methods of research. The objects of the study were 32 sexually mature, white, male rats, weighing 92 - 103 g, aged 4.5 months. Animals were injected with nalbupine intramuscularly once daily (at 10-11 a.m.) for 14 days. The initial dose of nalbuphine was 8 mg/kg during the first week, 15 mg/kg during the second week. It created the conditions of chronic opioid exposure. Before sampling, the animals were withdrawn from the experiment using dibutyl ether. Intervertebral discs of rats were used as a material for ultrastructural study. Ultrastructural specimens were prepared according to the accepted methods. The results of the study. As a result of the sampling after 7 days of opioid exposure we found inhomogeneous osmiophilicity and compaction of the nucleus pulposus matrix in which intensively accumulated osmiophilic grains of glycogen proteoglycans, increased the number of collagen fibers, some of them were heterogeneous. It was also noted the development of moderate degenerative changes in some notochondral cells, which was accompanied by increased vacuolization of the cytoplasm by inhomogeneous compaction of the nucleus and an increase of heterochromatin there. After 14 days necrotic changes in the cells of the nucleus pulposus, as well as the destruction of collagen fibers of the annulus fibrosus were found. In particular, an increase in the amount of heterochromatin in the nucleui of notochondral cells, which was accompanied by a decrease in the volume of the nucleui and inhomogeneous swelling of the cytoplasm. Active fibroblasts were often visualized in the annulus fibrosus. Intense osmiophilicity and thickening of collagen fibers of the annulus fibrosus were observed in some areas of the fibrous ring. Focal destruction of collagen fibers was also noted. In the areas of destruction the fibrils of collagen fibers disintegrated into an inhomogeneous fine-grained stratified mass and were located loosely. Conclusions. At the end of the first week we found that the cytoplasmic processes of chondrocytes decreased in volume, shortened, underwent fragmentation and destruction, some of them detached from the surface of the plasmolemma. At the end of the second week signs of opioid exposure progressed and manifested by an increase in the destruction of cytoplasmic processes in chondrocytes. Also focal destruction of collagen fibers was noted.